Healthcare utilization patterns before and after a long COVID diagnosis: a case-control study - Rick DeVoss; Elizabeth J. Carlton; Sarah E. Jolley; Marcelo C. Perraillon (BMC Public Health)
Abstract Background Documenting Long COVID cases has been challenging partly due to the lack of population-level data and uncertain diagnostic criteria, hindering the ability to ascertain healthcare utilization patterns over time. The objective of this study is to examine the characteristics and healthcare utilization patterns of Long COVID patients in Colorado pre- and post-diagnosis compared to controls. Methods Retrospective, longitudinal case-control study using a 100% sample of Colorado’s All-Payer Claims Database. The sample includes individuals 18 or older diagnosed with Long COVID between October 1, 2021, and August 1, 2022, with patients followed until August 2023. Long COVID was identified using the International Classification of Diseases, 10th Revision, U09.9 code in medical insurance claims. Analysis of healthcare utilization required one year of continuous enrollment before and after diagnosis. Controls were matched 2:1 on age group, sex, payer, and index month to account for contemporaneous trends in utilization. Results 26,358 individuals were ever diagnosed with Long COVID, resulting in a claims-based prevalence of 674 per 100,000 during the study period (population 3,906,402 individuals). Of these, 12,698 individuals had continuous enrollment and a Long COVID diagnosis: mean (SD) age, 59.0 (17.1); 65.3% female; 60.1% white; 83.0% residing in urban areas. The Long COVID sample was matched with 25,376 controls. Before diagnosis, 17% of Long COVID patients were hospitalized at least once, and 40% visited an emergency department on at least one occasion. Within the year following diagnosis, utilization of acute healthcare services significantly decreased relative to controls: hospitalizations, -6.1percentage points (p.p.), emergency department visits, -7.7 p.p., whereas outpatient services and medications increased: office visits, 3.6 p.p.; specialist office visits, 4.7 p.p.; and 5.2 new medications, (controls: 2.8). Changes in diagnoses of some conditions (e.g., metastatic carcinomas and lung cancer) were similar between groups. Conclusions and relevance Long COVID patients increased outpatient healthcare utilization following a diagnosis, switching from acute care settings. The change in service settings among this population suggests that diagnosis could lead to better patient management. Healthcare utilization among these patients is high, underscoring the need to understand the Long COVID burden on healthcare systems with population-level data.